Nonlinear guided wave technique for localized damage detection in plates with surface-bonded sensors to receive Lamb waves generated by shear-horizontal wave mixing. (March 2019) - Cho, Hwanjeong; Hasanian, Mostafa; Shan, Shengbo; Lissenden, Cliff J.
Abstract: Mutual wave interactions provide a very promising technique for nondestructive testing and evaluation due to their exceptional sensitivity to micro-scale damage growth in metallic materials. This article describes detection of localized fatigue damage in aluminum plates using polyvinylidene difluorine (PVDF) sensors to simultaneously receive shear-horizontal waves and the secondary Lamb waves that they generate. Finite element simulations explore several aspects of wave interaction and mode identification. Then laboratory experiments confirm secondary wave generation at the sum frequency in an aluminum plate using the PVDF sensor by conducting frequency-wave number domain and supporting analyses. The PVDF sensor enables computation of amplitude ratios even though the primary and secondary waves have different polarities. Finally, a simple guided wave technique based on electrically scanning the wave mixing zone around a plate is shown to detect early localized fatigue damage in an aluminum plate.